Effects of an individual 12-week community-located "start-to-run" program on physical capacity, walking, fatigue, cognitive function, brain volumes, and structures in persons with multiple sclerosis. (January 2019) - Feys, Peter; Moumdjian, Lousin; Van Halewyck, Florian; Wens, Inez; Eijnde, Bert O; Van Wijmeersch, Bart; Popescu, Veronica; Van Asch, Paul
Background: Exercise therapy studies in persons with multiple sclerosis (pwMS) primarily focused on motor outcomes in mid disease stage, while cognitive function and neural correlates were only limitedly addressed. Objectives: This pragmatic randomized controlled study investigated the effects of a remotely supervised community-located "start-to-run" program on physical and cognitive function, fatigue, quality of life, brain volume, and connectivity. Method: In all, 42 pwMS were randomized to either experimental (EXP) or waiting list control (WLC) group. The EXP group received individualized training instructions during 12 weeks (3×/week), to be performed in their community aiming to participate in a running event. Measures were physical (VO2max, sit-to-stand test, Six-Minute Walk Test (6MWT), Multiple Sclerosis Walking Scale-12 (MSWS-12)) and cognitive function (Rao's Brief Repeatable Battery (BRB), Paced Auditory Serial Attention Test (PASAT)), fatigue (Fatigue Scale for Motor and Cognitive Function (FSMC)), quality of life (Multiple Sclerosis Impact Scale-29 (MSIS-29)), and imaging. Brain volumes and diffusion tensor imaging (DTI) were quantified using FSL-SIENA/FIRST and FSL-TBSS. Results: In all, 35 pwMS completed the trial. Interaction effects in favor of the EXP group were found for VO2max, sit-to-stand test, MSWS-12, Spatial Recall Test, FSMC, MSIS-29, and pallidum volume. VO2max improved by 1.5 mL/kg/min, MSWS-12 by 4, FSMC by 11, and MSIS-29 by 14 points. The Spatial Recall Test improved by more than 10%. Conclusion: Community-located run training improved aerobic capacity, functional mobility, visuospatial memory, fatigue, and quality of life and pallidum volume in pwMS.